Examining prefrontal contributions to past- and future-oriented memory disturbances in daily life in dementia. (January 2021) - Liu, Lulu; Roquet, Daniel; Ahmed, Rebekah M.; Hodges, John R.; Piguet, Olivier; Irish, Muireann
Abstract: Deficits in episodic memory are commonplace in dementia, yet mounting evidence indicates pervasive impairments in future-oriented thinking in these syndromes. How such impairments manifest in the daily lives of people with dementia remain unclear, as do their neural bases. This study aimed to determine the neurocognitive mechanisms of past- and future-oriented memory performance across a large sample of dementia syndromes, each of which is characterised by distinct clinical and cognitive profiles. Carer-rated memory changes in everyday life in Alzheimer's disease, behavioural-variant frontotemporal dementia, semantic dementia, progressive non-fluent aphasia, and logopenic progressive aphasia were assessed using the Prospective and Retrospective Memory Questionnaire (PRM-Q). Participants underwent neuropsychological testing and whole-brain structural MRI. Relative to Controls, past- and future-oriented memory were compromised exclusively in AD and bvFTD, with no impairments reported for the other groups. For AD, atrophy in a distributed network of prefrontal, lateral and medial temporal regions including the hippocampus, correlated with past- and future-oriented memory impairments. In contrast, lateral and medial prefrontal regions correlated with past- and future-oriented memory difficulties in bvFTD. Notably, the orbitofrontal cortex emerged as a common neural substrate implicated in memory disturbances across the AD and bvFTD groups. This study confirms the presence of episodic amnesia in bvFTD across a host of everyday activities, mirroring the profile typically observed in AD. Of note, the orbitofrontal cortex emerged as a common region implicated in past- and future-oriented memory deficits in both patient groups, underscoring a critical role for prefrontal regions in supporting complex aspects of memory function in everyday life.